An Analysis of Mudhrabah Contract, Profit Sharing Rate, and Grant (Hibah) of Mudharabah Influence Customer’s Interest to do Saving Case Study: Muamalat Bank, Sragen Branch in 2017 - Kamaluddin, Imam; Cahyo, Eko Nur; Triani, Finis (AL-IKTISAB: Journal of Islamic Economic Law, 2018)
The purpose of this research is to analyze the influence of mudharaba contract, profit sharing rate and grant of mudharabah muthlaqah contract on customer’s interest to do saving and to ascertain how the mechanism of grant distribution on the mudharabah muthlaqah contract in Muamalat Bank of Indonesia, branch of Sragen. The findings are that Mudharaba Contract, Profit Sharing Rate and Grant on the Mudharabah contract, had influenced the customer’s interest to do saving in Muamalat Bank. Resulted that F test had shown F point as much as 2,783 with significant point as much as 0,165 more than 0.05, while determination coefficient was shown by R2 as much as 0.093 or 9,3% had influenced on the customer’s interest to do saving, while the 90,7% had influenced by other factor.